KEWAJIBAN PENGUSAHA MENYEDIAKAN ANGKUTAN ANTAR JEMPUT BAGI PEKERJA/BURUH PEREMPUAN YANG BERANGKAT DAN PULANG PADA MALAM HARI DI BALI SAFARI AND MARINE PARK - Udiana, I Made; Westra, I Ketut; Sri Utari, Ni Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p13, 2015)
This study examined the obligations of entrepreneur as stated in the regulations minister. By using normative method, this study showed the obligations of the entrepreneur in accordance with the laws and regulations governing between entrepreneurs and workers. By taking the case study of Bali Safari and Marine Park, which is located in Gianyar, Bali, it showed the significance of regulatory policies, the accompanying rights and obligations that was inherent in industrial relations.
Keywords: Entrepreneur, Obligation, Women Workers, Night Worker